Teaching about Christianity: a configurative review of research in English schools - Fancourt, N (Taylor and Francis, 2016)
This article presents a systematic review of empirical research on teaching about Christianity in state schools in England between 1993 and 2013. First, I explain the background to this religion’s current place within English religious education. The value of a configurative review is set out, and inclusion criteria are outlined, leading to the selection of 58 publications. Then the article’s theoretical frame is explained, drawing on activity theory, and the analysis is set out under three broad organising principles: (1) Teachers’ professional and pedagogical intentions; (2) How teachers draw on different pedagogical strategies to enact these intentions, for example systematic or thematic approaches; and (3) How these intentions and strategies affect pupil learning, such as pupils’ conceptions of difficult topics. The implications for research in religious education are then drawn together, notably the need to consider the pedagogical issues for different religions individually.